Analisis Perbandingan Pengaruh Sistem Lingkungan terhadap Residen di IPWL BUKIT DOA melalui Perspektif Teori Sistem - Anita Maisaroh; Yolanda Oktari Br Bangun; Rachel Yohana Vatreciya Purba; Rizky Akbar; Muhammad Aqsha Rangkuti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Rehabilitation is crucial in aiding the recovery of drug addicts, emphasizing that the rehabilitation system influences individual behavior. The impact of a positive environmental system, including family support for the recovery of drug abuse victims, is very important. This research also explores the relationship between the rehabilitation system and resident behavior, aiming to enhance the effectiveness of rehabilitation programs and the well-being of residents. The 9-month recovery program at IPWL Bukit Doa aims to rehabilitate residents from drug addiction. The study emphasizes the importance of a positive environmental system in the recovery of individuals from drug abuse. Family support and a good environment are essential for successful recovery. This research also highlights the influence of the rehabilitation system on resident behavior, with the goal of improving the effectiveness of rehabilitation programs. The research shows that the 9-month recovery program is not always successful due to poor environments and lack of family support. The environment plays a significant role in individual behavior, with 74% being influenced by the environment. Although the 9-month recovery program at IPWL Bukit Doa aims to prevent relapse, the success of relapse prevention is not guaranteed due to environmental factors such as lack of family support and unsupportive environments often triggering relapse.